Hubungan antara Celebrity Worship dengan Body Image pada Penggemar Blackpink - Tumanan, Gabriela; Rahayu, Maria Nugraheni Mardi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aims to identify the correlation between celebrity worship of the idol group Blackpink and the body image of Blackpink fans (Blink). Celebrity worship is a phenomenon that happens because of human interaction with social media, and body image is a self-image that a person owns. There were 216 subjects in this study with an age range of 15-24 years. The sampling technique used was purposive sampling. This study collected data using the Celebrity Attitude Scale (CAS) and The Multidimensional Body-Self Relation Questionnaire-Appearance Scale (MBSRQ-AS). Data analysis used the Spearman correlation test. The results of the data analysis showed that the social entertainment dimension of celebrity worship showed a significant positive relationship with body image (r = 0.217, p <0.05). Then, the dimension of intense personal feeling from celebrity worship also shows a significant positive relationship with body image (r = 0.243, p <0.05). The last dimension, borderline pathological celebrity worship, also shows a significant positive relationship with body image (r = 0.260, p <0.05). It can be concluded that celebrity worship has a relationship with body image.